In vitro meristem-tip culture and regeneration approaches in Congolese cassava accessions (Manihot esculenta Crantz cv. Boma and cv. Mpelo-Nlongi) - Mukiese, J.-Roger Bansimba; Ndofunsu, AimÃ© Diamuini; Bulubulu, Freddy; Ntumbula, Alexandre Mbaya; Ndiku, SÃ©bastien Luyindula (International Journal of Biological Research, 2015)
Shiny dome-like structures measuring less than 1mm in length were excised aseptically from shoot tip buds of infected of two cassava (Manihot esculenta Crantz) local cultivars (Boma and Mpelo Nlongi) and cultivated in vitro in two types of media with different combination of growth hormone: Murashige and Skoog supplemented of sucrose (20 g/l), Naphtalenacetic acid (NAA, 10 Î¼M), Ben-zylaminopurine (BAP, 0.66 Î¼M) as well as Gibberellic acid (GA3, 0.1 Î¼M) with 80 mg/l of Adenine sulphate and MS-free growth regulators. After four weeks, data were scored: 29.5% responding explant with callus formation and 20.5% responding explants to shoot development in the medium with growth regulators for the cultivar Boma whereas the cultivar Mpelo-Nlongi presented 5.7% and 25.7% respectively of callus formation and shoot development. The cultivar Boma presented a tendency more pronounced for the callus formation rather than with the shoot development contrary to the cultivar Mpelo-Nlongi. In regards of this experiment, it was shown that the media composition and genotype are essential factors, which influence in vitro growth, mainly the shoot development, in the culture of meristems for cassava local accessions.